2004
DOI: 10.1536/jhj.45.799
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Blood Pressure Reduction on Oxygen Uptake Kinetics at the Onset of Exercise in Hypertensive Patients

Abstract: SUMMARYThe aim of the present study was to investigate the adverse effects of hypertension on the cardiovascular system in daily activities and the effect of acute blood pressure reduction on oxygen (O 2 ) uptake kinetics.Twenty hypertensive patients were included in the study group. Patients performed treadmill exercise tests (2.5 km/hour and 5 inclines) twice, before and after blood pressure reduction with sublingual captopril. In the control group, ten hypertensive patients underwent two tests one hour apar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…It has been shown, that T2DM influences cardiac mechanoenergetic efficiency and cardiac hypertrophy [30][31][32][33]. The respective medication in the T2D c and T2D p group might have improved cardiac function, as has been supposed in previous studies [9][10][11]. However, as can be observed in ▶Fig.…”
Section: Groupmentioning
confidence: 75%
See 3 more Smart Citations
“…It has been shown, that T2DM influences cardiac mechanoenergetic efficiency and cardiac hypertrophy [30][31][32][33]. The respective medication in the T2D c and T2D p group might have improved cardiac function, as has been supposed in previous studies [9][10][11]. However, as can be observed in ▶Fig.…”
Section: Groupmentioning
confidence: 75%
“…This is in line with the results of the T2D p and T2D group, in the present study. Taniguchi et al [10] showed a positive effect of beta blockers (after one year of treatment) and Dayi et al [11] for ACE inhibitors (administered shortly before the exercise test) on V'O 2 pulm kinetics in hypertensive subjects and in patients with dilated cardiomyopathy. They explained this effect by improved cardiac function (improved left ventricular ejection fraction).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Níveis de aptidão cardiorrespiratória baixos podem interferir diretamente nas atividades de vida diária desses pacientes e como verificado por Dayi et al 12 , durante as atividades diárias a fadiga é comum em pacientes com hipertensão e que isso ocorre mesmo quando baixos níveis de exercícios são exigidos. Lim et al 13 afirmam que a capacidade de exercício é 30% menor em pacientes hipertensos se comparados com normotensos.…”
Section: Discussionunclassified